2009
DOI: 10.1007/s11250-009-9350-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary folate and vitamin B12 supplementation and consequent vitamin deposition in chicken eggs

Abstract: We determined the effects of dietary supplementation with folate and vitamin B(12) on lipid metabolism and the deposition of these vitamins in eggs of laying hens (age 64-72 weeks). Four levels of folate (0, 0.5, 4 and 10 mg/kg) and three levels of vitamin B(12) (0, 0.01 and 0.08 mg/kg) were added to the basal diet for 8 weeks in a 4 x 3 factorial completely randomized design study. No significant physiological interaction between folate and vitamin B(12) was evident under our experimental conditions. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…In terms of egg folate concentration and indices of folate status, our results were again similar with results from earlier studies (Sherwood et al, 1993;House et al, 2002;Hebert et al, 2005;Roth-Maier and Böhmer, 2007;Bunchasak and Kachana, 2009;Hoey et al, 2009;Dickson et al, 2010;Tactacan et al, 2010). The concentration of folate in eggs from birds supplemented with FA (10 or 100 mg of FA/kg of diet) increase significantly (approximately twice as much) compared with that of birds fed the control diet.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of egg folate concentration and indices of folate status, our results were again similar with results from earlier studies (Sherwood et al, 1993;House et al, 2002;Hebert et al, 2005;Roth-Maier and Böhmer, 2007;Bunchasak and Kachana, 2009;Hoey et al, 2009;Dickson et al, 2010;Tactacan et al, 2010). The concentration of folate in eggs from birds supplemented with FA (10 or 100 mg of FA/kg of diet) increase significantly (approximately twice as much) compared with that of birds fed the control diet.…”
Section: Discussionsupporting
confidence: 90%
“…The concentration of folate in eggs from birds supplemented with FA (10 or 100 mg of FA/kg of diet) increase significantly (approximately twice as much) compared with that of birds fed the control diet. This increase however was similar between 10 or 100 mg of FA/kg of supplemented diets, demonstrating the saturable characteristic of egg folate concentration when dietary FA was increased (Sherwood et al, 1993;House et al, 2002;Hebert et al, 2005;Roth-Maier and Böhmer, 2007;Bunchasak and Kachana, 2009;Hoey et al, 2009). Hebert et al (2005) supplemented as much as 128 mg of FA/kg of the laying hen diet but did not find any significant increase in egg folate concentration beyond the concentration achieved at 4 mg of FA/kg in the diet.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Another interesting finding of these authors is that egg yolk folate bioavailability is 100% if compared folic acid and that this folate content in enriched eggs is stable during storage at 4 °C for 4 weeks (House et al, 2002). Recent studies also describe a similar egg folate deposition model with significant increases on addition of a small dose of folic acid, which reaches a plateau (Bunchasak and Kachana, 2009;Hoey et al, 2009). In the Bunchasak and Kachana (2009) study, yolk folate content in the hens fed 10.31 mg folate/kg diet was higher by about 40% than that in the hens fed a basal diet (0.31 mg/kg diet).…”
Section: Folate Enrichmentmentioning
confidence: 99%
“…These strategies include the development of novel foods enriched with natural folates (12) . Recently, several groups have shown that the folate content of eggs can be increased significantly by supplementing the diet of laying hens with folic acid (43)(44)(45)(46)(47)(48) . Most of the additional folate appears in the eggs in the natural form, mainly as 5-methyltetrahydrofolate (48) .…”
mentioning
confidence: 99%